Routledge handbook on Arab media - Mīlādī, Nūr al-Dīn; Mellor, Noha, 1969- (Routledge handbooks., 2021)
"This Handbook provides the first comprehensive reference book in English about the development of mass and social media in all Arab countries. Capturing the historical as well as current developments in the media scene, this collection maps the role of media in social and political movements. Contributors include specialists in the field from North America, Europe, and the Middle East. Each chapter provides an overview of the history, regulatory frameworks and laws governing the press, and socio-political functions of the media. While the geopolitical complexities of the region have been reflected in the expert analyses collectively, the focus is always the local context of each member state. All 37 chapters consider the specific historical, political and media trajectories in each country, to provide a contextual background and foundation for further study about single states or comparative analysis in two or more Arab states. Capturing significant technological developments and the widespread use of social media, this all-inclusive volume on Arab media is a key resource for students and scholars interested in journalism, media and Middle East studies"--